2012
DOI: 10.1242/dev.086645
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor AP-2γ is a core regulator of tight junction biogenesis and cavity formation during mouse early embryogenesis

Abstract: The trophectoderm epithelium is the first differentiated cell layer to arise during mammalian development. Blastocyst formation requires the proper expression and localization of tight junction, polarity, ion gradient and H2O channel proteins in the outer cell membranes. However, the underlying transcriptional mechanisms that control their expression are largely unknown. Here, we report that transcription factor AP-2γ (Tcfap2c) is a core regulator of blastocyst formation in mice. Bioinformatics, chromatin immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 59 publications
10
92
0
Order By: Relevance
“…We found that TFAP2C is initially widely expressed in the preimplantation embryo, and then, during the morula to blastocyst transition, it becomes enriched in the mural trophectoderm and downregulated in the ICM. Notably, this expression pattern was largely consistent with the role of TFAP2C in tight junction biogenesis and blastocoel formation (Choi et al, 2012), suggesting that TFAP2C is a key trophectoderm-specific transcription factor in the preimplantation embryo. Here we report that TFAP2C plays a much wider regulatory role in early lineage formation.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…We found that TFAP2C is initially widely expressed in the preimplantation embryo, and then, during the morula to blastocyst transition, it becomes enriched in the mural trophectoderm and downregulated in the ICM. Notably, this expression pattern was largely consistent with the role of TFAP2C in tight junction biogenesis and blastocoel formation (Choi et al, 2012), suggesting that TFAP2C is a key trophectoderm-specific transcription factor in the preimplantation embryo. Here we report that TFAP2C plays a much wider regulatory role in early lineage formation.…”
Section: Introductionsupporting
confidence: 72%
“…We recently established that TFAP2C is a key regulator of genes required for blastocyst formation in mice (Choi et al, 2012). TFAP2C-depleted embryos arrest around the morula stage and fail to establish the trophectoderm epithelium.…”
Section: Tfap2c Is Required For the Initiation Of Zygotic Cdx2 Expresmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the proximal putative AP-2-binding site is the cis-acting element essential for Girdin transcription. AP-2 is a developmentally regulated transcription factor family that is crucial for the expression of genes such as tight junction regulators during vertebrate development (Choi et al, 2012;Eckert et al, 2005). To evaluate the involvement of AP-2 in Girdin transcription, we next co-transfected the Girdin promoter −891/+41 construct and an AP-2α expression vector into HepG2 cells, which express a low level of endogenous AP-2α and are therefore suitable for AP-2 overexpression studies (Braganca et al, 2003).…”
Section: Ap-2 Regulates Girdin Transcriptionmentioning
confidence: 99%